Pengukuran Jatidiri dan Daya Saing Koperasi dengan Pendekatan Development Ladder Assesment (DLA) Studi pada KUD Subur, KPRI Universitas Brawijaya - Dermawanto, Agus Tri; Maryunani, .; Noor, Iswan (Jurnal Aplikasi Manajemen, 2015)
The aim of this study is to analyze theoretically that the Development LadderAssesment DLA variables in which could be a measurement tool for the identity and competitivenessof a cooperation. The concept of DLA in this study is applied in order to categorizethe cooperation in which has the identity between KUD Subur, KPRI Brawijaya Universityand KWSU BAM. The object of the study is Koperasi Unit Desa (KUD), KPRI BrawijayaUniversity and KWSU BAM in Malang. The subjects of this study are the senior members ofmanagement, leader, and members, or at least two members. Data collection was performedby interviewing in a group discussion using a questionnaire. The analysis method uses DLAapproach with variable vision, capacity,resources, and network, as well as DLA approachwith Daniel Cote models and ICA ROAP Grid Model. From the finding, it is found that KUDSubur is on the yellow zone means KUD Subur in performance is generally satisfactory, butit needs indicators in order to improve the organization management. KPRI Brawijaya Universityand KWSU BAM is at the green zone, it means KPRI Brawijaya University and KWSUBAM performance has been good in terms of vision, capacity, and network resources. Danielcote model analysis, KUD Subur, KPRI Brawijaya University and KWSU BAM in general arein quadrant I. KWSU BAM has a very good performance in applying the identity of cooperativesand doing well in the competition.